Defining the role of acyl-CoA synthetase 6 on α-synucleinopathy - Smaltz, Amber (East Carolina University, 2022)
Background: Neurodegenerative diseases known as [alpha]-synucleinopathies, most notably dementias and Parkinson's Disease (PD), are characterized by neuronal aggregation and accumulation of [alpha]-synuclein ([alpha]-syn) in a manner that is deleterious to neurological health. Endogenous [alpha]-syn is involved in many cellular processes including synaptic vesicle homeostasis, the modulation of dopamine biosynthesis, and chaperone vesical exocytosis and neurotransmission. However, excessive [alpha]-syn accumulation in an aggregated form can be detrimental to cellular health. A known modulator of [alpha]-syn aggregation is docosahexaenoic acid (DHA), an omega-3 polyunsaturated fatty acid highly enriched in the brain. While DHA is well established as a neuroprotective molecule eliciting a wide range of neuroprotective benefits, a controversy exists regarding DHA's role in [alpha]-syn biology. Specifically, free DHA has been speculated to bind with [alpha]-syn in a manner that exacerbates aggregation, potentially causing Lewy body formation. Contrary to this notion, dietary DHA is well known to elicit neuroprotection in models of synucleinopathy. To address this controversy, we have leveraged our lab's recent discovery that long-chain acyl-CoA synthetase 6 (ACSL6) is responsible for the neuronal membrane enrichment of DHA. We have shown that loss of ACSL6, and consequent ~50% loss in neuronal membrane DHA, has a detrimental impact on cognitive function. This thesis aims to utilize our DHA-deficient model to elucidate the impact of DHA metabolism by ACSL6 in [alpha]-syn accumulation. Hypothesis: We hypothesized that in the absence of ACSL6-mediated DHA metabolism, [alpha]-syn aggregation would increase. This hypothesis is rooted in our postulated mechanism that ACSL6 enzyme action pulls free DHA out of [alpha]-syn oligomers to reduce accumulation and ultimately promote neuroprotection. Methods: To test this hypothesis, the role of ACSL6 in [alpha]-syn accumulation was assessed in our novel model of neuronal membrane DHA depletion due to the loss of ACSL6 (ACSL6KO mice) combined with a model of [alpha]-syn accumulation due to overexpression of a mutated form of the human [alpha]-syn protein (hA53Tsyn transgenic mouse model). This [alpha]-syn mutation (A53T) was originally identified in individuals with PD as it increases the accumulation of [alpha]-syn and the risk of developing PD. Western blot analysis of brain tissue was utilized to determine if [alpha]-syn accumulation was brain region specific, and if the accumulation occurred more in the membrane or cytosolic fraction. Results: As a result of combining ACSL6 loss with [alpha]-syn overexpression (ACSL6KO-hA53Tsyn mice), we observed a remarkable reduction in lifespan by 62%, an average lifespan of 5 months in ACSL6KO-hA53Tsyn when compared to the hA53Tsyn model which has average lifespan of 13 months, (control mice live to 28 months). Tissues were harvested from control, hA53Tsyn, and ACSL6KO-hA53Tsyn at 3.5 months of age, prior to average onset of ACSL6KO-hA53Tsyn lethality. The [alpha]-syn levels as monomers and as oligomers (i.e., complex aggregates) were compared via western blot analysis from soluble (cytosolic) and insoluble (membrane) fractions. The brain tissue of ACSL6KO-hA53Tsyn compared to hA53Tsyn mice had higher [alpha]-syn monomer protein abundance and increased oligomerization of [alpha]-syn in ACSL6KO-hA53Tsyn in the soluble fraction. Comparison of brain regions known to accumulate [alpha]-syn (cerebellum, cortex, and brain stem), revealed that [alpha]-syn protein accumulation was the most affected in the ACSL6KO-hA53Tsyn cortex. Next, to determine if [alpha]-syn aggregated uniformly throughout the cortex, the cortex of a 3.5-month-old ACSL6-hA53Tsyn mouse was divided into 5 sections, rostral to caudal. The most rostral region of the cortex (i.e., prefrontal cortex) was found to have the highest levels of monomer and oligomer of [alpha]-syn. Plasma was isolated from blood samples to determine if [alpha]-syn aggregated in the periphery, and an increase was observed in the aged hA53Tsyn (EShA53Tsyn) mice. Conclusion: Our data demonstrate a critical role of ACSL6, a known DHA-metabolizing enzyme, in the accumulation of [alpha]-syn and the survival rates in a model of [alpha]-synucleinopathy.
Keywords: acyl-coa synthetase; α-synuclein; lipid; metabolism; Synucleinopathies; Coenzyme A Ligases